The Turkish Version of Multidimensional Assessment of Fatigue and Fatigue Severity Scale is Reproducible and Correlated With Other Outcome Measures in Patients With Systemic Sclerosis - Kevser GÖK,; Gizem CENGİZ,; Kemal EROL,; Salih ÖZGÖÇMEN, (Archives of Rheumatology, 2016)
Objectives: This study aims to evaluate the reproducibility of Turkish versions of multidimensional assessment of fatigue (MAF) and fatigue severity scales (FSS) and the relationship between health related quality of life, disability, and psychological status in patients with systemic sclerosis (SSc). Patients and methods: A total of 21 female patients (mean age 47.14±10.39 years; range 18 to 75 years) who met 2013 American College of Rheumatology/European League Against Rheumatism criteria for SSc were evaluated for severity of organ involvement and symptoms. Turkish version of MAF, FSS, and visual analog scale of fatigue were assessed at baseline and after two to three weeks. Level of dyspnea was noted and disability, functional limitation, and quality of life were assessed by health assessment questionnaire, 6-minute walking distance, and short-form 36, respectively. Results: Ten patients had diffuse and 11 had limited SSc. MAF subscales and FSS had significant correlations with short-form 36-vitality subscale and 6-minute walking distance. Intraclass correlation coefficients for FSS and visual analog scale of fatigue were 0.824 (95% confidence interval, 0.566- 0.929) and 0.932 (95% confidence interval, 0.832-0.972), respectively. The intraclass correlation coefficients for MAF subscales changed between 0.916 and 0.968, except for MAF-timing (intraclass correlation coefficient, 0.404). Conclusion: Our results revealed that FSS and MAF subscales had high reproducibility and correlated well with quality of life and disability scales which, to some extent, may suggest convergent validity of MAF subscales and FSS in SSc. The incompatible nature and four-choice answering in two items of MAF-timing may be the underlying reason for trivial relationship with other parameters. The Turkish version of MAF and FSS may be used to assess fatigue in patients with SSc.